El lexema "angustia" en un corpus de la literatura costarricense - Jones León, Sonia (2005)
This article analyzes the presence of the lexeme "anguish" and its influence in the construction of meaning in two tales from the book "Stories of Anguish and Landscapes" of Carlos Salazar Herrera: "A Scream" and "The Road".